Root and Canal Morphology of Mandibular Second Molar in an Iranian Population by Clearing Method - Zare Jahromi, M (Shiraz University of Medical Sciences, 2013)
Statement of Problem: The knowledge of the pulp anatomy plays an important role in the success of endodontic treatments. Purpose: The aim of this study was to determine the root and canal morphology of the mandibular second molar teeth in an Iranian population. Material and Methods: One hundred intact human mandibular second molars were collected. The teeth were examined visually and the number of their roots were recorded. The teeth were covered using of lacquer. Access cavities were prepared and the pulp tissue was dissolved by sodium hypochlorite. The apices were covered with the glue and the root canals were injected with the methylene blue and were decalcified with 10% nitric acid, dehydrated with ascending concentrations of alcohol and rendered clear by immersion in methyl salicylate. The following remarks were evaluated: (i) number of root canals per tooth; (ii) number of canals per root; (iii) canal configuration in each root. Results: Of 100 examined teeth; 6% had one root, 89% had two roots, 2% had three roots and 3% had C-shaped roots. The teeth were classified based on the number of canals: 3 % had single canal, 6 % two canals, 54% three canals, 34% four canals, whilst 3 % had C-shaped roots. Based on the Vertucci classification, the most prevalent canal configuration in the mesial root was type II and in the distal root was type I. Conclusion : Iranian mandibular second molar teeth exhibit features which are similar to the average Jordanian, Caucasian and Burmese root and canal morphology.